2013
DOI: 10.6090/jarq.47.237
|View full text |Cite
|
Sign up to set email alerts
|

Chrysanthemum Stunt Viroid

Abstract: The chrysanthemum stunt viroid (CSVd) is a small, single-stranded, infectious RNA forming a circular secondary structure, which belongs to the Pospiviroidae family and mainly infects certain species and cultivars of Compositae and Solanaceae. The effects on cultivated chrysanthemum are severe, including stunting of plant height, reduced flower size, and flower color bleaching. However, the expression of the symptoms depends on the chrysanthemum cultivars. CSVd is known to be readily transmitted by sap, but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 45 publications
2
21
0
3
Order By: Relevance
“…CSVd has been included in the EPPO A2 list of quarantine pathogens ( OEPP/EPPO, 2014 ). CSVd infection causes various adverse effects on diseased Chrysanthemum plants including stunted growth, short internodes, poor root development, reduced flower size, and flower color bleaching, consequently resulting in the production of unmarketable plants and low yield of flowers ( Horst et al, 1977 ; Chung et al, 2001 ; Jeon et al, 2012 ; Matsushita, 2013 ; Savitri et al, 2013 ). Symptoms such as yellow deformed leaves with terminal necrosis, flower distortion, or leaf necrosis were observed on CSVd-infected Argyranthemum ‘Butterfly’ plants ( Marais et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…CSVd has been included in the EPPO A2 list of quarantine pathogens ( OEPP/EPPO, 2014 ). CSVd infection causes various adverse effects on diseased Chrysanthemum plants including stunted growth, short internodes, poor root development, reduced flower size, and flower color bleaching, consequently resulting in the production of unmarketable plants and low yield of flowers ( Horst et al, 1977 ; Chung et al, 2001 ; Jeon et al, 2012 ; Matsushita, 2013 ; Savitri et al, 2013 ). Symptoms such as yellow deformed leaves with terminal necrosis, flower distortion, or leaf necrosis were observed on CSVd-infected Argyranthemum ‘Butterfly’ plants ( Marais et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…One such disease is chrysanthemum stunt, incited by chrysanthemum stunt viroid (CSVd) [1,2,3]. Symptoms of a CSVd infection include stunting, spotted leaves, poor rooting, flower color change, and disturbance of photoperiodic responses related to flowering initiation [4,5,6,7,8,9]. The CSVd is a member of the genus Pospiviroid, within the family Pospiviroidae, which has a central conserved region and replicates and accumulates in the nuclei [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have demonstrated the existence of resistance in commercial cultivars in Japan [21,22,23,24,25]. Since CSVd and infected plants are widely distributed, and a symptomless alternative host could be the source of the disease [8,26], chrysanthemum production has always been adversely affected by CSVd contamination. Consequently, CSVd resistance, which could withstand unforeseen contamination, would be a desirable trait.…”
Section: Introductionmentioning
confidence: 99%
“…Chrysanthemum stunt viroid (CSVd), a member of the family Pospiviroidae ( Bouwen and van Zaayen, 2003 ), can attack several ornamental crops, including Chrysanthemum ( Bouwen and van Zaayen, 2003 ), Argyranthemum ( Zhang et al, 2015 ), Dahlia ( Nakashima et al, 2007 ), and Petunia ( Verhoeven et al, 1998 ). Infection by CSVd can result in unmarketable plants and low yield of flowers ( Marais et al, 2011 ; Jeon et al, 2012 ; Matsushita, 2013 ; Savitri et al, 2013 ; Zhang et al, 2015 ), and possibly to considerable losses. CSVd is also listed as one of the quarantine pathogens in the European Union’s Plant Health Directive (2000/29/EC) ( Cho et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%